What Calls to ARMs? International Evidence on Interest Rates and the Choice of Adjustable-Rate Mortgages - Badarinza, Cristian; Campbell, John Y.; Ramadorai, Tarun (Management Science, 2018)
The relative popularity of adjustable-rate mortgages (ARMs) and fixed-rate mortgages (FRMs) varies considerably both across countries and over time. We ask how movements in current and expected future interest rates affect the share of ARMs in total mortgage issuance. Using a nine-country panel and instrumental variables methods, we present evidence that near-term (one-year) rational forecasts of future movements in ARM rates do affect mortgage choice, particularly in more recent data since 2001. However, longer-term (three-year) rational forecasts of ARM rates have a relatively weak effect, and the current spread between FRM and ARM rates also matters, suggesting that households are concerned with current interest costs as well as with lifetime cost minimization. These conclusions are robust to alternative (adaptive and survey-based) models of household expectations. Data, the online appendix, and the institutional appendix are available at https://doi.org/10.1287/mnsc.2016.2629 . This paper was accepted by Amit Seru, finance.